Synthesis, structure, and magnetic properties of a family of Mn(II) compounds with substituted 2-aminopyridinium ions. (1st July 2021) - Carnevale, David J.; Dawe, Louise N.; Landee, Christopher P.; Turnbull, Mark M.; Wikaira, Jan L.
Graphical abstract: Complexes formed from the reaction of Manganese (II) halides with substituted 2-aminopyradine resulted in connected metal halide chains or metal halide ladders through short halide…halide contacts. The substitutions studied include 3-methyl (3MAP), 5-methyl (5MAP) or 5-iodo (5IAP). The resulting complexes showed weak antiferromagnetism. Abstract: A family of complexes were made by combining MnX2 ·nH2 O (X = Cl, Br) with 2-amino-3-methylpyridine (3MAP), 2-amino-5-methylpyridine (5MAP) or 2-amino-5-iodopyridine (5IAP) in aqueous acidic conditions. The resulting complexes were (3MAPH)2 Cl2 .MnCl2 (H2 O)2 (1 ), (3MAPH)2 Br2 .MnBr2 (H2 O)2 (2 ), (5IAPH)8 [Mn4 Cl10 (H2 O)8 ] Cl6 (3 ) and (5MAPH)2 MnBr4 (4 ). Complexes 1 –3 crystalize in monoclinic space groups (1 = P 21 / c, 2&3 = P 21 /n) with chains formed by halide bridged manganese ions. Compound 4 crystalizes in the triclinic space group P -1 with a manganese halide ladder structure formed via short Br…Br contacts. Complexes 1, 2 and 4 were studied through variable temperature magnetic susceptibility measurements, all of which exhibited weak antiferromagnetic interactions (J = – 0.45 to –0.05 K).